How is the acyl chain composition of phosphoinositides created and does it matter?. (28th October 2019) - Barneda, David; Cosulich, Sabina; Stephens, Len; Hawkins, Phillip
Abstract: The phosphoinositide (PIPn) family of signalling phospholipids are central regulators in membrane cell biology. Their varied functions are based on the phosphorylation pattern of their inositol ring, which can be recognized by selective binding domains in their effector proteins and be modified by a series of specific PIPn kinases and phosphatases, which control their interconversion in a spatial and temporal manner. Yet, a unique feature of PIPns remains largely unexplored: their unusually uniform acyl chain composition. Indeed, while most phospholipids present a range of molecular species comprising acyl chains of diverse length and saturation, PIPns in several organisms and tissues show the predominance of a single hydrophobic backbone, which in mammals is composed of arachidonoyl and stearoyl chains. Despite evolution having favoured this specific PIPn configuration, little is known regarding the mechanisms and functions behind it. In this review, we explore the metabolic pathways that could control the acyl chain composition of PIPns as well as the potential roles of this selective enrichment. While our understanding of this phenomenon has been constrained largely by the technical limitations in the methods traditionally employed in the PIPn field, we believe that the latest developments in PIPn analysis should shed light onto this old question.